Analisis Kepemimpinan Partisipatif dalam Pengendalian Kebakaran Hutan dan Lahan - Desie Andreastuti (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
Tropical forests in Palangka Rraya city is a tremendous asset givenin view of the forest can provide economic beneﬁ ts as a foreigPendapatan Asli Daerah (PAD ) in addition it is also the sector with the most potentialas a source of livelihood and life for society and private plantationcompanies . However, the existence of forests are currently threatened due to forest areas that were once green became barren and the barren region that is mainly caused by human activity that is that is doing the destruction and land by burningburning the land . Land and forest ﬁ res occur each year into problems and threats faced by the multidimensional impact forests. In order For to supporting local government in realizing the land and forest ﬁ re control,  based on the Regional RegulationPeraturan Pemerintah No. 7 of 2003 is related to the preparation of the land and forest ﬁ re control and decision of the Mayor of Palangkaraya No. 11 of 2008 while the duties and functions of the head of Head of the Environment AgencyBadan Lingkungan Hidup (BLH) by Peraturan WalikotaMayor Regulation Palangkaraya No. 17 of 2012 on job descriptions positions of Chairman of the Environment AgencyBLH Palangkaraya is formulating operational policy body, controlling, developing, organizinge, coordinating e and providinge technical services in the ﬁ eld of environmental management are integrated with the together-together relevant agencies in accordance with the provisions and applicablelaws.the laws that apply. This study will explore participatory leadership style used by the Head of BLH Palangkaraya in control of land and forest ﬁ res . Eﬀ orts made by the Head of BLH Palangkaraya is to involve members of the organization in BLH Palangkaraya to be active to control land and forest ﬁ res.